2020
DOI: 10.1111/bph.15290
|View full text |Cite
|
Sign up to set email alerts
|

Factor H‐related protein 1: a complement regulatory protein and guardian of necrotic‐type surfaces

Abstract: Factor H-related protein 1 (FHR-1) is a member of the factor H protein family, which is involved in regulating innate immune complement reactions. Genetic modification of the encoding gene, CFHR1 on human chromosome 1, is involved in diseases such as age-related macular degeneration, C3glomerulopathy, and atypical hemolytic uremic syndrome, indicating an important role for FHR-1 in human health. Recent research data demonstrate that FHR-1 levels increase in IgA nephropathy and ANCA vasculitis and that FHR-1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…We demonstrated that FHR1, MFHR13 and the MFHR1 variants are able to bind not only to C5 and C5b6, but also to C6, C7, C8 and C9. The binding to C8 and C9 was significantly higher compared to C5b6, which suggest that regulation is not only mediated through C5b6-complex binding, as currently assumed (12). Our observations indicate an FHR1 activity resembling the function of vitronectin, which is a soluble regulator of the MAC (66), and thus contributes to the understanding of the mechanism of action of FHR1.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…We demonstrated that FHR1, MFHR13 and the MFHR1 variants are able to bind not only to C5 and C5b6, but also to C6, C7, C8 and C9. The binding to C8 and C9 was significantly higher compared to C5b6, which suggest that regulation is not only mediated through C5b6-complex binding, as currently assumed (12). Our observations indicate an FHR1 activity resembling the function of vitronectin, which is a soluble regulator of the MAC (66), and thus contributes to the understanding of the mechanism of action of FHR1.…”
Section: Discussionsupporting
confidence: 50%
“…The C-terminal region of FH (FH 19-20 ) is highly conserved in all FHRs, while none of them contains regions homologous to FH 1-4 (8). Of particular interest is FHR1, a regulator of C5 activation, which inhibits the last steps of the complement cascade (terminal pathway) and the MAC formation (10, 12).…”
Section: Introductionmentioning
confidence: 99%
“…On human endothelial cells, C3b opsonization becomes more pronounced with increasing concentrations of FHR-1 and FHR-1(SV) ( Figure 6A), which impressively highlights the context-dependent role of FHR-1. Context dependent roles of FHR-1 have also been described in other reports for apoptotic and necrotic cells [reviewed in (50,51)]. Whether the observed inhibitory effect toward the C3 and the C5 convertases plays an important physiological role in vivo must be questioned for two reasons.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly plasma distributed regulators can also attach to surfaces. For example, both plasma regulators, Factor H and FHR1, bind to the glomerular basement membrane (Skerka et al 2020).…”
Section: C5bmentioning
confidence: 99%